2020
DOI: 10.1136/annrheumdis-2020-217381
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in immune checkpoint inhibitor-induced polymyalgia rheumatica

Abstract: Contributors KSMvdG, RHJAS and EB contributed to conception or design of the work. KSMvdG and RHJAS contributed to acquisition of data. All authors contributed to analysis or interpretation of data. All authors were involved in drafting of the work or revising it critically for important intellectual content. All authors provided final approval of the version published. All authors agreed to be accountable for all aspects of the work in ensuring that questions related to the accuracy or integrity of any part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…A [18F]-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) scan was performed during prednisolone-free remission in two subjects (figure 1B). These follow-up scans showed markedly lower FDG uptake scores when compared with the previously reported scans obtained at the diagnosis of ICI-PMR 5. Thus, the FDG-PET/CT scan confirmed that the ICI-PMR had subsided in both patients.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…A [18F]-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) scan was performed during prednisolone-free remission in two subjects (figure 1B). These follow-up scans showed markedly lower FDG uptake scores when compared with the previously reported scans obtained at the diagnosis of ICI-PMR 5. Thus, the FDG-PET/CT scan confirmed that the ICI-PMR had subsided in both patients.…”
supporting
confidence: 72%
“…Grading: 0, no uptake; 1, uptake lower than liver; 2, uptake equal to liver; 3, uptake higher than liver 7. For comparison, the previously reported FDG uptake scores at diagnosis of ICI-PMR are also shown 5. Dx, diagnosis; FDG, [18F]-fluorodeoxyglucose; ICI, immune checkpoint inhibitor; IFX, infliximab (for autoimmune colitis); INJ, injection of shoulder (for ICI-PMR); NSAID, nonsteroidal anti-inflammatory drug; PET, positron emission tomography; PMR, polymyalgia rheumatica; VED, vedolizumab (for autoimmune colitis).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Keeping in mind the costs and radiation burden of FDG-PET/CT, this imaging modality could be applied in selected cases: for instance, patients with atypical presentation, or patients with strong clinical suspicion but a negative US or MRI scan. Recently, it was suggested that FDG-PET/CT may also aid the diagnosis of the PMR-like syndrome developing upon immune checkpoint inhibitor therapy for cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) may show synovitis, tenosynovitis, bone marrow edema, and erosions (31). In PMR, ultrasound may show subdeltoid and subacromial bursitis, trochanteric bursitis, or biceps tenosynovitis (32,33). Ultrasound and MRI may also suggest other diagnoses, such as crystalline arthritis, OA, and noninflammatory musculoskeletal conditions.…”
Section: Physical Examinationmentioning
confidence: 99%